Food price spikes temporary, inflation likely to fall in 2022 - Glauber, Joseph W.; Smith, Vincent H. (American Enterprise Institute, 2022)
Consumer prices have increased substantially in recent months. According to the Bureau of Labor Statistics, the Consumer Price Index (CPI) for All Urban Consumers rose 7.0 percent for the 12 months ending December 2021, the largest increase since the 12-month period ending June 1982.1 The average price of the basket of foods consumed both at home and away from home (in fast food and other outlets) has also increased. The year-over-year CPI for food increased 6.3 percent in December, the highest 12-month increase since October 2008, and prices for food at home rose by 6.5 percent. Some food categories such as red meats saw inflation rates between 15 and 18 percent (Figure 1), but prices for other groups such as dairy products increased modestly. Food purchases account for about 12 percent of total consumer expenditures, while prices for all food (consumed both at and away from home) account for just 14 percent of the economy-wide CPI. Nevertheless, higher food prices have important consequences, especially for low-income families that spend higher shares of their incomes on food. So, it is important to understand what has happened to both consumer and farm gate prices over the past 24 months and place those shifts in a broader historical context. Most economists understand that price increases are driven by supply shocks, including supply-chain disruptions, and increases in the overall (aggregate) demand for all goods and services, fueled often by low interest rates (expansionary monetary policy) and, typically only in the short run, increases in public spending. Both factors have clearly been at play over the past 12 months.